1996
DOI: 10.1017/s003329170003378x
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and Alzheimer's disease: a population-based study in Saguenay-Lac-St-Jean/Québec (IMAGE Project)

Abstract: SynopsisThe birth distribution of 399 cases of Alzheimer's disease (AD) identified in the region of Saguenay-Lac-St-Jean (Québec) was compared with that of: (a) the population currently living in the area; and (b) the population born during the same period in the area. AD cases have been recruited since 1986 by the IMAGE Project. Cases and controls were grouped according to the month of birth and according to the day of birth using density estimation. Analyses showed a significant deficit of births in the mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…These include Alzheimer's disease [12,13], subgroups of individuals with attention deficit hyperactivity disorder [14], autism [15][16][17], Down's syndrome [18], dyslexia [19], eating disorders [20] and multiple sclerosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…These include Alzheimer's disease [12,13], subgroups of individuals with attention deficit hyperactivity disorder [14], autism [15][16][17], Down's syndrome [18], dyslexia [19], eating disorders [20] and multiple sclerosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the Southern Hemisphere, the pattern is shifted by about half a year (10). An excess number of spring births is found among patients suffering from autistic disorders (11), Down's syndrome (12), and Alzheimer's disease (13). In Sweden and Great Britain, spring-born children experience a higher risk of developing insulin-dependent diabetes (14,15).…”
Section: Differences In Adult Lifespan By Month Of Birthmentioning
confidence: 99%
“…In the Northern Hemisphere, these include studies by Dysken et al [10] in Minnesota (n = 727, autopsy confirmed); Vitiello et al [11] in Maryland (n = 150); Lawlor et al [12] in Ireland (n = 215); Fratiglioni et al [13] in Sweden (n = 98); Prince et al [14] in England (n = 31), and Vézina et al [15] in Canada (n = 399). In the Southern Hemisphere, Henderson et al [16] reported no significant seasonal birth pattern for 170 individuals with Alzheimer's disease, including 143 who had been born in the Southern Hemisphere.…”
Section: Alzheimer's Diseasementioning
confidence: 99%